Effect of Tetrahydrofuran Extraction on Surface Functional Groups of Coking Coal and Its Wettability - Jian Yao; Huaijun Ji; Huazhang Lu; Tongtong Gao (Journal of Analytical Methods in Chemistry)
Coking coal was extracted with tetrahydrofuran solvent using ultrasonic and microwave-assisted method at 50°C and atmospheric pressure. Wettability of raw coal and its residue (residual coal) was tested with capillary penetration method. The raw and residual coals were studied by Fourier transform infrared spectroscopy (FTIR) with curve-fitting analysis. The variation of main surface functional groups of coking coal before and after extraction and its effect on wettability were analyzed. The results were obtained as the following: after extraction with tetrahydrofuran, hydroxyl, ether oxygen, and carbonyl in the coal structure were dissolved, the content of hydrophilic functional groups reduced, and then the hydrophobicity of coal enhanced. At the same time, part of aliphatic hydrocarbon dissolved, the length of aliphatic chains (I2) decreased from 3.961 of raw coal to 3.636 of residual coal, the length of aliphatic chains became shorter, aliphatic CH2 side-chains decreased and aliphatic CH3 side-chains increased, and hydrophobic functional groups content increased. In the aromatic structure, four hydrogens per ring increased and two, three, and five hydrogens per ring decreased. Reduction of substitution functional groups and aliphatic hydrocarbon decreased with the side-chains breakage produce more active sites, which increases the degree of condensation of the aromatic ring (I3). The combined action of the decrease of the hydrophilic functional groups and the increase of the hydrophobic functional groups made the wettability of the coking coal become weak.